2001
DOI: 10.1128/jb.183.24.7067-7075.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Essential Amino Acids in theAzorhizobium caulinodansFucosyltransferase NodZ

Abstract: The nodZ gene, which is present in various rhizobial species, is involved in the addition of a fucose residue in an ␣1-6 linkage to the reducing N-acetylglucosamine residue of lipo-chitin oligosaccharide signal molecules, the so-called Nod factors. Fucosylation of Nod factors is known to affect nodulation efficiency and host specificity. Despite a lack of overall sequence identity, NodZ proteins share conserved peptide motifs with mammalian and plant fucosyltransferases that participate in the biosynthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…The first R in this motif is invariant among all three fucosyltransferase families (Fig. 4A) and is essential for the activity of a1,6-and a1,2-fucosyltransferases in vitro and in vivo (18,19,21). We mutated this R in OFUT1, making OFUT1 R245K and OFUT1 R245A .…”
Section: E and F)mentioning
confidence: 98%
See 1 more Smart Citation
“…The first R in this motif is invariant among all three fucosyltransferase families (Fig. 4A) and is essential for the activity of a1,6-and a1,2-fucosyltransferases in vitro and in vivo (18,19,21). We mutated this R in OFUT1, making OFUT1 R245K and OFUT1 R245A .…”
Section: E and F)mentioning
confidence: 98%
“…Because the ER lacks detectable GDP-fucose transporter activity, we thought that OFUT1 might facilitate Notch folding independently of its fucosyltransferase activity. A comparative study of sequences from a1,2-fucosyltransferases and a1,6-fucosyltransferases identified a GXHXR(R/H) motif that is implicated in donor substrate binding (18,19); O-fucosyltransferases include a related motif (20). The first R in this motif is invariant among all three fucosyltransferase families (Fig.…”
Section: E and F)mentioning
confidence: 99%
“…Of these WbsJ and α1,2-FucT from H. pylori have unique substrate specificities and have demonstrated applicability in the synthesis of relevant fucose containing oligosaccharides [14, 16]. Regardless of the species that the α1,2- FucT was cloned from, no structural information is yet available for the α1,2-FucT subfamily (unlike the evolutionary related α1,6-FucT subfamily) [17]. As such, our understanding of the α1,2-FucT mechanism and roles of specific amino acid motifs are limited and are based off the available α1,6-FucT and α1,3-FucT crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…The known α3-FucTs and α4-FucTs classify in a different GT family (GT10) not included in the FucT superfamily. This superfamily is characterized by the presence of three conserved peptide regions (called motifs I, II, and III) [14],[64],[75] (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%